Clinical triad with multi‐biopsy histopathology as a reliable diagnostic marker of mycetomas: a retrospective review from a tertiary care center. (28th August 2022) - Ansari, Farzana; Singh, Saurabh; Bhardwaj, Abhishek; Budania, Anil; Bains, Anupama; Nalwa, Aasma; Khera, Sudeep; Elhence, Poonam; Patel, Ankur; Yadav, Taruna; Khera, Pushpinder
Abstract: Background: Mycetoma is a neglected tropical infectious disease which runs a prolonged and protracted course. Microbiological confirmation is diagnostic yet unreliable due to poor sensitivity and variable availability of culture facilities in resource poor settings. Methods: A retrospective review was performed on electronic records (histopathology, microbiology, and radiology) of all patients who underwent skin biopsies with mycetoma as one of the clinical differential diagnoses from year 2016 to 2020. Results: Out of 73 patients biopsied with a differential of mycetoma, 42 fit the clinical triad of swelling‐sinuses‐granules. After clinical, microbiological, pathological, and radiological correlation, 31 cases were of eumycetoma and seven were of actinomycetoma. Mean patient age was 37.58 ± 13.8 years with a male to female ratio 2.45 : 1 and mean disease duration of 11.31 ± 10.9 years. Histopathological findings revealed fungal hyphae in 18 cases and gram‐positive bacteria in six cases. Fungal culture was positive in 13 cases with the three commonest organisms being Madurella mycetomatis in five cases, Fusarium and Aspergillus nidulans in two cases each. X‐ray changes of soft tissue, bones, and joints were seen in 25 cases, and "dot‐in‐circle" sign was seen in eight of nine MRIs. Conclusion: Eumycetoma was more common than actinomycetoma in our setup, ratio being 4.43 : 1. A clinical triad of swelling, multiple sinuses and grainy discharge with any one diagnostic support (histopathology/radiology) is sufficient to make a definitive diagnosis of mycetoma in the absence of microbiological identification.